Strotz Meets Allais: Diminishing Impatience and the Certainty Effect: Comment - Saito, Kota (American Economic Review, 2011)
Halevy (2008) states the equivalence between diminishing impatience (i.e., quasi–hyperbolic discounting) and the common ratio effect. The present paper shows that one way of the equivalence is false and shows the correct and general relationships: diminishing impatience is equivalent to the certainty effect and that strong diminishing impatience (i.e., hyperbolic discounting) is equivalent to the common ratio effect. JEL: D81